Viabilidade de criação de uma RPPN no Parque Ecológico Quedas do Rio Bonito - Morel, Jean Daniel (2015)
This research studied the viability of establishing a Particular Reserve of Natural Patrimony - Reserva Particular do Patrimônio Natural - RPPN - in Quedas do Rio Bonito Ecological Park, located in Lavras, Minas Gerais. In spite of being called “Ecological Park” it is not in accordance to any category of conservation unit legally described in the law. The methodology of literature review and the documental research study were used. The federal and state legislations on RPPN, as well as technical and scientific works were reviewed together with documents related to the subject. Later, considerations were made regarding the situation of RPPN, in relation to the Brazilian legislation and about the possibility of transforming part of the studied area in this category of unit of conservation. It was concluded that the transformation of the area into a RPPN is an important instrument for the conservation of the local biodiversity. The results allow concluding that it is viable to implant a RPPN in the area of the Park, by delimiting an area in its interior and by taking into consideration the existing utilization zones.